NONINVASIVE BRAIN STIMULATION INCREASES THE COMPLEXITY OF RESTING-STATE BRAIN NETWORK ACTIVITY IN OLDER ADULTS. (11th November 2018) - Zhou, J; Lo, O; Halko, M; Harrison, R; Lipsitz, L; Manor, B
Abstract: Successful completion of cognitive and motor tasks requires functional interactions between numerous brain networks over multiple temporal scales. Biological aging reduces the multi-scale "complexity" of the spontaneous fluctuations in network activity. Still, it is unknown if such "resting-state" complexity is sensitive to functional status, or modifiable via intervention. We hypothesized that resting-state complexity is lower in older adults with functional limitations, and, that it can be increased via repeated exposure to transcranial direct current stimulation (tDCS). Twelve older adults with mild-to-moderate executive dysfunction (i.e., Trail Making Test B time below the 25th percentile of age- and education-based norm) and slow gait (i.e., gait speed <1.0m/s), along with 12 age- and sex-matched controls, completed a baseline resting-state fMRI. Ten participants within the functionally-limited group then completed a 2-week, 10-session tDCS (n=6) or sham (n=4) intervention targeting the left dorsolateral prefrontal cortex (dlPFC). A follow-up fMRI was acquired 2–3 days following intervention. The complexity of seven well-established functional networks was quantified by averaging the 'multiscale entropy' of the blood-oxygen-level-dependent time-series across all voxels within each network. Compared to controls, older adults with functional impairments exhibited lower complexity in the motor, ventral attention, executive and limbic networks (F>4.7, p<0.04). Within this group, exposure to real tDCS, compared to sham, increased the complexity within the executive and limbic networks (F>4.9, p<0.04). These results suggest the older adults with functional limitations exhibit lower resting-state complexity, and, that repeated exposure to tDCS targeting the left dlPFC may increase such complexity within this vulnerable cohort.